Ответы и объяснения

2013-02-21T16:07:19+00:00

 

 

 

 

 

 

 

(х + 1) : 51 - 11 = 65

(х + 1) : 51 = 76 

 

 х + 1 = 76 * 51 = 3876

х = 3875

(3875 + 1) : 51 - 11 = 65

 

 (х + 1) : 51 - 11 = 3 

 

 (х + 1) : 51 = 14

 

 х + 1 = 14 * 51 = 714

х = 713

 

 (713 + 1) : 51 - 11 =3

 

 

 (х + 1) : 51 - 11 = 18

 

 (х + 1) : 51 = 29

х + 1 = 1479

 

 х = 1478

 

 (1478 + 1) : 51 - 11 = 18

 

 

 (х + 1) : 51 - 11 = 9

(х + 1) : 51 = 20

 

 х + 1 = 1020

х = 1019

(1019 + 1) : 51 - 11 =9

 

 

(х + 1) : 51 - 11 = 12 

 

 (х + 1) : 51 = 23

 

 х + 1 = 1173

х = 1172

(1172 + 1) : 51 - 11 =12